Experimental investigation of the tensile properties of steel foam hollow sphere assemblies - Kalpakoglou, Thomas; Constantinides, Georgios; Yiatros, Stylianos (My University, 2025)
The present research aims to study the mechanical properties of steel foam hollow sphere assemblies of various relative densities under the effect of uniaxial tensile loading, evaluating the validity of a new test protocol and comparing it with other experimental results. Through a series of experiments with different groups of specimens, which were recorded step by step, the effects of factors such as the relative density and the number of bonds on the mechanical properties of the specimens were identified, and their impact on the response discussed. The shape of the specimen is cubic with dimensions 50 × 50 × 50 mm3. The range of values recorded in this research for the Elastic Modulus is 340,89–399,28 MPa, and for Tensile Strength is 2,8-3,53 MPa, as exhibited by the five different groups of specimens tested in the present study with relative density from 0,059 to 0,074. The promising experimental results support the proposed methodology and test protocol for studying similar assemblies under tensile loading and an attempt to explain the differences between past scaling equations and experimental results. Scanning electron microscopy (SEM) is also performed and presented to examine the microstructure of the specimens and the crack surface.
Keywords: Elastic modulus; Metal foam; Scanning electron microscopy (SEM); Steel foam hollow sphere assemblies; Tensile loading; Tensile strength